Personal Data Protection in West Java's Digital Public Services: An Analysis of Implementation Post-PDP Law - Berna Ermaya Sudjana; Ihsanul Maarif (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Transformation service digital public in West Java is growing rapidly and increasing efficiency service , but also gives rise to complexity risk related personal data protection community . Publishing Constitution Personal Data Protection (PDP Law) becomes runway law important For strengthen right privacy citizens and​ organizing data governance in the sector public . Research This aim analyze implementation of the PDP Law in service West Java digital public with review three dimensions Main : regulatory , institutional , and technical-operational . Research methods use approach descriptive qualitative through studies documents , review regulations , and interviews with the apparatus involved in data management . Research results show that implementation the beginning of the PDP Law provides a number of impact positive , such as increasing awareness institutional to importance personal data protection , improvements procedure data management through implementation principle data minimization , as well as update policy privacy on a number of digital platforms. However , the findings also identified various challenges , among others, have not yet composition regulations derivatives at the level area , the minimum officials Data Protection Officer (DPO), inequality standard security application , limitations literacy apparatus , as well as weakness mechanism monitoring and reporting incident data leak . Novelty research This lies in the approach integrative that combines analysis regulatory , institutional , and technical-operational in a way simultaneously , so that produce greater understanding​ comprehensive about dynamics implementation of the PDP Law at the level area . This study give contribution important for development of a more public data governance model accountable , adaptive , and sustainable in support digital transformation of government .